Koperasi syariah dan pengaturannya di Indonesia / Burhanuddin S. ; editor Musleh Herry, Muhammad Idris. - BURHANUDDIN S.; Muhammad Idris; Musleh Herry (UIN-Maliki Press, 2013)
x, 370 hlm. : ilus. ; 21 cm [3 eks.]